Angiomatous meningioma in Sturge–Weber syndrome. Issue 6 (June 2015) - Ahmed, Zubair; Prayson, Richard A.
Abstract We report a case of an intraventricular angiomatous meningioma arising in a 3-year-old boy diagnosed with Sturge–Weber syndrome (SWS) who presented with intractable epilepsy and right-sided hemiparesis. He underwent surgical resection of the epileptogenic focus. Histologic sections showed the typical findings of SWS accompanied by adjacent mild focal cortical dysplasia (International League Against Epilepsy Type Ib pattern; Palmini et al. Type IA). A small intraventricular mass, which was incidentally noted on imaging studies, was also excised. The mass showed a prominent venous vasculature with intermixed meningothelial cells, consistent with an angiomatous meningioma World Health Organization Grade I. SWS is a rare, sporadically occurring disorder marked by a port wine stain (hemangioma of the skin) arising in the distribution of the trigeminal nerve accompanied by an angiomatous proliferation in the leptomeninges. The underlying cortex often shows prominent dystrophic mineralization and gliosis. Patients often present with seizures and may require surgical resection when seizures prove to be pharmacoresistant. Meningiomas in SWS are a rare occurrence (only one known previously reported case) and angiomatous meningioma in SWS has never been described. The literature is briefly reviewed and the pathogenesis of hemangiomas in SWS and its implication in angiomatous meningioma is discussed.